THE PHARMACIST’S ROLE IN THE DISPENSING METHYLFENIDATE IN THE TREATAMENT OF ADHD IN CHILDREN (REMUNOM, 2024)
Methylphenidate is widely used in the treatment of children with Attention Deficit Hyperactivity Disorder (ADHD), offering significant improvements in attention, control of hyperactivity and reduction of impulsivity. However, its use is associated with several side effects and risks, including insomnia, loss of appetite and potential impacts on growth and cardiovascular health, highlighting the importance of pharmaceutical attention. Continuous guidance from the pharmacist is essential to optimize treatment adherence, identify and manage adverse effects, and ensure safe and effective medication administration. This study reviews the existing literature on the role of pharmaceutical care in the management of ADHD with methylphenidate, presenting evidence that pharmaceutical intervention can significantly improve therapeutic outcomes and quality of life for pediatric patients. The integrated approach, which combines the use of methylphenidate with behavioral and educational interventions, is also highlighted as an effective strategy for promoting coping and self-regulation skills in children.